The management of fragility fractures of the hip: a quality assessment project - Kauta, Ntambue (Department of Health and Rehabilitation Sciences, 2017)
Introduction: Fragility fractures of the hip (FFH) constitute the most serious complication of osteoporosis carrying a mortality rate of up to 20 – 30% in the first year after injury and are associated with post injury decay in patient's level of activity in more than 50% of the cases. It is also a predictor of future osteoporosis related fractures. Surgical fixation of the hip fracture within 48 of admission, multimodal pain management, deep vein thrombo-prophylaxis, early physical therapy, appropriate assessment and management of osteoporosis and frailty in a multidisciplinary approach are the standard of care for FFH to keep the mortality and morbidity rate as low as possible and prevent future fragility fractures. Aim: To assess the standard of care of FFH at our institution and determine areas of care which need more attention and improvement. Methods: Retrospective review of clinical and radiographic records of all patients admitted at our level 1 trauma unit for fragility fracture of the hip from 1st January 2014 to 31st December 2014. The waiting time from admission to surgical fixation of the hip fracture, pain control and thrombo-prophylaxis strategies, the rate of geriatric referrals and the extent of osteoporosis management were assessed. Results: We admitted 113 fragility fractures of the hip from 1st January to 31st December 2014. Ninety- eight clinical records and 98 pelvis radiographs were included in the study. The other 15 clinical records were incomplete and were therefore excluded. The average waiting time from admission to surgery was 49 hours (range 9 -120). Low dose morphine, paracetamol and tramadol were the only perioperative pain control medication used for all patients. All patients had low molecular weight heparin and compression stockings prescribed for thrombo-prophylaxis. Only 2 (2, 04%) of patients had some osteoporosis investigations ordered. There were no geriatric referrals made and no formal osteoporosis management in all reviewed records. Conclusion: While the waiting time from admission to surgery was largely within the recommended time frame, there were no signs of a multidisciplinary approach to the management of fragility fractures of the hip at our institution leaving osteoporosis and frailty largely untreated.